THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND TECHNOLOGICAL INNOVATION ON EMPLOYEE PERFORMANCE AT THE DISTRICT INSPECTORATE. JEMBER: THE ROLE OF ORGANIZATIONAL CULTURE AS A MEDIATING VARIABLE - Siti Mualfa; Nursaid Nursaid; Abadi Sanosra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of transformational leadership and technological innovation on the performance of Jember Regency Inspectorate employees, with organizational culture as an intervening variable. The research used an explanatory quantitative approach by collecting data through questionnaires to Inspectorate employees. Data analysis was carried out using path analysis with the help of SmartPLS. The results of the study show that transformational leadership and technological innovation have a significant effect on employee performance and organizational culture. Organizational culture also has a significant influence on performance and is able to mediate the relationship between transformational leadership and technological innovation on employee performance. These findings confirm that the success of performance improvement is not only determined by leadership and technology, but also by the strength of an organizational culture that supports integrity, collaboration, innovation, and accountability